Respuesta :
x + y = 65 The sum of two numbers (x and y) is 65
x - y = 27 The difference of the two numbers is 27
This can easily be solved with elimination.
2x = 92
x = 46
Then we solve for y replacing the x value for x.
46 + y = 65
y = 19
The solution is (46, 19).
If you want substitution:
x + y = 65
x - y = 27
y = 65 - x
x - y = 27
x - (65 - x) = 27
x - 65 + x = 27
2x - 65 = 27
2x = 92
x = 46
Then solve for y using either equation.
46 - y = 27
- y = - 19
y = 19
We get the same solution (46, 19). You can check this by plugging in the x and y values into one or both equations.
x - y = 27 The difference of the two numbers is 27
This can easily be solved with elimination.
2x = 92
x = 46
Then we solve for y replacing the x value for x.
46 + y = 65
y = 19
The solution is (46, 19).
If you want substitution:
x + y = 65
x - y = 27
y = 65 - x
x - y = 27
x - (65 - x) = 27
x - 65 + x = 27
2x - 65 = 27
2x = 92
x = 46
Then solve for y using either equation.
46 - y = 27
- y = - 19
y = 19
We get the same solution (46, 19). You can check this by plugging in the x and y values into one or both equations.
The numbers whose sum is 65 and the difference is 27 are 46 and 19 and this will be determined by forming the linear equation in two variables.
Given :
- The sum of the two numbers is 65.
- The difference between the two numbers is 27.
Let 'x' represent the greater number and let 'y' represent the lesser number.
The sum of the two numbers is given by:
[tex]x + y = 65[/tex] --- (1)
The difference between the two numbers is given by:
[tex]x - y = 27[/tex]
[tex]x = 27+y[/tex] ----- (2)
Now, put the value of 'x' in equation (1).
[tex]27+y+y = 65[/tex]
27 + 2y = 65
2y = 38
y = 19
Now, put the value of 'y' in equation(2).
x = 27 + 19
x = 46
Therefore, the numbers are 46 and 19.
For more information, refer to the link given below:
https://brainly.com/question/19770987